2019
DOI: 10.1016/j.fertnstert.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neonatal outcomes of very low birth weight infants by mode of conception: in vitro fertilization versus natural pregnancy

Abstract: After adjustment for maternal and neonatal baseline characteristics, infants born as singletons earlier than 28 weeks after IVF more frequently had high-stage retinopathy of prematurity than those born after NP, whereas infants born as multiplets between 28 and 31 weeks after IVF had fewer major congenital anomalies, high-grade intraventricular hemorrhage, and periventricular leukomalacia than those born after NP. Otherwise, no differences in mortality and neonatal outcomes were found. Conclusion(s):Very low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
1
10
2
1
Order By: Relevance
“…Th erefore, this increase has been attributed to infertility itself and underlaying factors associated to infertility rather than ART [19,33]. In accordance with our results, Heo et al [6] demonstrated that the incidence of major congenital anomalies in infants born as singletons aft er IVF was not higher than that in those born aft er NP aft er adjusting for confounding factors. As pointed out by the authors and in accordance with our recent results, the more generalized use of preimplantation genetic screening procedures may contribute to a lower incidence of congenital anomalies aft er ART procedures [35,36].…”
Section: One Of the Sources Of Perinatal Complications (Especiallysupporting
confidence: 89%
See 1 more Smart Citation
“…Th erefore, this increase has been attributed to infertility itself and underlaying factors associated to infertility rather than ART [19,33]. In accordance with our results, Heo et al [6] demonstrated that the incidence of major congenital anomalies in infants born as singletons aft er IVF was not higher than that in those born aft er NP aft er adjusting for confounding factors. As pointed out by the authors and in accordance with our recent results, the more generalized use of preimplantation genetic screening procedures may contribute to a lower incidence of congenital anomalies aft er ART procedures [35,36].…”
Section: One Of the Sources Of Perinatal Complications (Especiallysupporting
confidence: 89%
“…Over the course of the last decades, a substantial number of children have been conceived aft er applying assisted reproductive technology (ART) procedures [1,2]. It has been generally assumed that pregnancies achieved aft er ART have a higher prevalence of obstetric and perinatal complications such as prematurity and low birthweight neonates and a higher prevalence of cesarean sections at delivery [3][4][5][6][7]. Such perinatal complications could be a direct consequence of the higher rate of multiple pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that even singleton pregnancies conceived after IVF-ET are more likely to develop prematurity, gestational hypertension, placental abruption, low birth weight and intrauterine growth retardation [6][7][8][9][10]. The risk of adverse outcomes originating from suboptimal placentation in pregnancies after IVF-ET is significantly greater than that in spontaneously conceived pregnancies [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This positive trend is due to more appropriate embryo transfer strategies, milder ovarian stimulation, laboratory technological advances, and improved culture media [5]. However, even in singleton pregnancy, after adjustment for maternal confounding factors, the risk of multiple adverse outcomes during the perinatal period, including miscarriage, preterm birth, small for gestational age, low birth weight and gestational hypertension, are higher in IVF-ET pregnancies than in spontaneously conceived pregnancies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This success rate is variable from 45% in patient having less than 35 years to 7% in patients having more than 42 years age which is due to the poor response of ovary to stimulation or hyperstimulation syndrome (7). Different previous studies have investigated the maternal or neonatal outcomes of ART (8)(9)(10)(11)(12)(13)(14). These studies have reported various problems in neonates concieved by ART or their mothers including multiple gestation, preterm labor, low birth weight and intra-uterine growth retardation (IUGR).…”
Section: Introductionmentioning
confidence: 99%